Adherence to Clinical Trial Supported Evaluation of Optic Neuritis. (3rd September 2019) - Meer, Elana; Shindler, Kenneth S.; Yu, Yinxi; VanderBeek, Brian L.
ABSTRACT: Purpose : The Optic Neuritis Treatment Trial showed that an MRI of the brain is a powerful predictor of developing multiple sclerosis (MS). However, surveys of practitioners suggest that the recommended use of imaging is not consistently followed in practice. With this study, we aim to assess the rate at which newly diagnosed optic neuritis (ON) patients receive brain MRIs. Methods : This is a retrospective cohort study using administrative medical claims data from a large, national US insurer. All incident cases from 2000 to 2016 of ON in patients without MS were assessed. The primary outcome was a comparison of patterns of MRI scanning usage following diagnosis of ON. Secondary outcomes evaluated steroid treatment and progression to MS. Results : Of 2865 qualified ON patients, 1755 (61.3%) received a brain MRI. At 1 year follow-up, 629 (30.3%) patients had progressed to MS, a rate that increased slightly to 34.3% (366 patients) within a 3-year period of their initial ON diagnosis. A total of 520 (18.2%) patients received intravenous steroids, and 383 (13.4%) received oral steroids within 30 days of the ON diagnosis. Conclusion : Across the United States, a surprisingly low number of individuals obtain a brain MRI following onset of ON, suggesting that physicians may not be fully assessing the risk of MS.